2018
DOI: 10.1007/s11751-018-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in detection of radiolucent foreign bodies in extremities

Abstract: Removal of foreign bodies from soft tissues in emergency is very challenging and becomes more problematic when it is radiolucent. Blind exploration is sometimes hazardous for patients especially when it is in proximity to a vessel or a nerve or an overlying tendon. The purpose of this study was to determine the accuracy of ultrasonography (USG) in detecting radiolucent soft tissue foreign bodies in the extremities. From January 2014 to January 2016, 120 patients with either a positive history or clinically sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…USG failed to detect a deep FB which was observed by MRI due to soft tissue infection and fluid collection around a small piece of sponge. A similar case was reported with a different scenario after two years from the injury [17]. Previous comparative studies of different radiological investigations were done in vitro.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…USG failed to detect a deep FB which was observed by MRI due to soft tissue infection and fluid collection around a small piece of sponge. A similar case was reported with a different scenario after two years from the injury [17]. Previous comparative studies of different radiological investigations were done in vitro.…”
Section: Discussionsupporting
confidence: 53%
“…Although early diagnosis and prompt removal of foreign bodies are required to prevent complications, there is no consensus related in the approach of detecting of FBs. Recently a procedure is reported in the literature at identifying FBs [17,33,34]. Although radiography holds excellent sensitivities for radiopaque foreign bodies, the accuracy, sensitivity, and positive predictive value of ultrasound in detection of non-radiopaque FBs were found as 94%, 99% and 94%, respectively [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Radiolucent foreign bodies are visualized as hyper-echoic foci with accompanying acoustic shadows. 8 In ultrasonography, acoustic shadowing can differentiate foreign body from scar tissue, gas bubble and normal intermuscular fascia, because they are void of acoustic shadowing. Accuracy, sensitivity and positive predictive value for foreign bodies by ultrasonography were determined as 94.16%, 99.08% and 94.13%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy, sensitivity and positive predictive value for foreign bodies by ultrasonography were determined as 94.16%, 99.08% and 94.13%, respectively. 8 The authors suggested that ultrasonography should be considered in non-healing wound to screen for underlying foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic has been successfully been applied for freezing, cavitation, emulsification and thermosonication for many types of food products [5][6][7]. Several investigationson foreign body detection using ultrasonic sensor had been carried out as reported by Correia et al [8], Zhao et al [9], Pallav et al [10],Leemans and Destain [11], Tantray et al [12] and Polat et al [13], Mcclements [14],Hassler and Homayoon [15], Le Coz et al [16],Iuliano [17], Liu et al [18], Liaw et al [19], Makinde et al [20], Holmes et al [21], Melo et al [22], Khan et al [23], Prabhakar et al [24],Rodrigues et al [25], Franchini et al [26], Pandey [27], Aftab et al [28], Gounder and Tan [29], Sadaka et al [30], Fasina et al [31], Khan et al [32], Mitev et al [33], Roux et al [34], Nakib et al [35], Rathore [36], Singleton et al [37], Mahesh et al [38], Ezenwa [39], Natung [40] and Mustapha [41], In this paper, two common foreign bodies materials e.g. steel and rubber with different sizes were used to investigate the sensor voltage and voltage loss at the ultrasonic receiver.…”
Section: Introductionmentioning
confidence: 99%